Meningkatkan Aktivitas, Keterampilan Kerja Sama dan Hasil Belajar Siswa Muatan IPS Materi Peristiwa Kebangsaan Seputar Proklamasi Kemerdekaan Dengan Menggunakan Pembelajaran BISA di Kelas V SD Negeri 1 Tanjung - Suhaimi; Zahra Shufia Zulfah (CV. ITTC INDONESIA, 2024)
This study identifies issues such as low levels of engagement, collaboration skills, and student learning outcomes during the learning process. To address these challenges, efforts have been made to implement the BISA model in classroom activities. The research aims to outline teacher activities, assess student engagement, analyze collaboration skills, and evaluate student learning outcomes. Conducted as Classroom Action Research (PTK), the study spanned four sessions in a fifth-grade class at SD Negeri 1 Tanjung, involving 12 students (8 boys and 4 girls) in the second semester of the 2023/2024 academic year. The findings indicate significant improvements: teacher activity scores increased to a very good level of 32, student engagement achieved an active participation rate of 100%, collaboration skills were highly proficient at 100%, and student learning outcomes improved by 100%. Consequently, it can be concluded that employing the BISA learning model enhances teacher and student engagement, collaboration skills, and learning outcomes. These findings offer a viable option for selecting and implementing effective learning models, particularly in the context of social studies education.